Improving Scientific Generic Skills Through Implementation of Model SSCS (Search, Solve, Create, and Share) in Concept of Classification of Living Things in MTsN Model Banda Aceh - Dewi Febriyanty; Suhrawardi Ilyas; Cut Nurmaliah (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2014)
Search, solve, create and share (SSCS) learning model  can help students to evolve some generic skills namely spoken, coorporation, and problem solving skills. Those skills are the aspects of assessment to evaluate the achievement of teaching learning process that implements SSCS models. The study was aimed to determine the increase in student achievement, scientific generic skills, and correlation between the skills and the learning outcomes  of students of class VII of MTsN Model Banda Aceh in 2013 in concept of classification of living things  throught implementing SSCS model. The study used experimental method with randomized control group pretest - posttest design . The study used two classes experimental-group and control-group classes chosen according to pretest scores. Data was collected pretest, posttest and scientific generic assessment The results showed that the value of tcount ttable  (5,8 1,6). This indicated that there was a significant increase in students learning outcome. The value of t-count of communication aspect (1),  coorporation aspect (2,7), and problem solving skills (3,4). The correlation among  communication , cooperation  and problem solving skills was high ( r = 0,7).  Therefore it can be concluded that there were increases in student achievement and scientific generic skills and correlation between scientific generic skills and cognitive student learning outcomes except communication aspect.